Dynamic Response Analysis of Frontal Crash on Vehicle Against Lighting Column Using FEM - Ibrahim @ Tamrin, Mohd Norihan; Ismail, Nurul Hayati; Ismail, Al Emran (Journal of Advanced Mechanical Engineering Applications, 2021)
A collision between a car and a rigid object on the street, such as an electrical pole or lighting column, may pose a major risk to the the car driver and passengers. It is critical to investigate the collision of a vehicle with a rigid body, particularly the deformation of the vehicle’s frontal region against a lighting column at various speeds. In this study, the deformation and dynamic response of the vehicle’s frontal area are calculated and analyzed using the ANSYS finite element approach. According to the numerical analysis of frontal impact, a speed of 80 km/h results in a total deformation of 0.0713 m, while a velocity of 120 km/h results in a total deformation of 0.10218 m. When the vehicle is traveling at a higher speed, the lighting column causes additional deformation to the frontal region of the vehicle. Because of the significant internal energy generated during a collision, the car absorbs more impact energy than the lighting column due to the aluminium alloy’s material properties.